The Implementation of Simple Vlog Media to Improve Self-Confidence Characters of Primary School Students During the Covid-19 Pandemic - Saefudin, Asep; Setiawan, Wawan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Self-confidence is a character that human beings should have and develop in their life. Through character, we can express our opinions smoothly, do things calmly, and can also become leaders for those who lack confidence. Lack of self-confidence in students can hinder the achievement of the learning process. The lack of self-confidence is based on many factors, one of which is an inaccurate learning strategy. During the Covid 19 pandemic, students carried out the full learning process from their respective homes. This makes the teacher have to determine the appropriate learning strategy to increase the character of students’ confidence. One of the strategies is the scientific approach in which the learning stages have aspects presenting the learning results. This is the successful key to build a confident character in students with positive support from their parents. This study was aimed to foster students’ self-confidence through simple vlog media where students continuously trained to perform in front of the camera with high self-confidence. The study was conducted on primary school students in West Bandung. The method used in the study was the descriptive qualitative with interactive analysis technique. The findings showed that primary school students were able to perform confidently through simple vlog media that they uploaded to social media. Over time, the students’ confident character significantly improved visibility in the vlog.